Employing an R Software Package rsm for Optimizing of Genistein, Daidzein, and Glycitein Separation and Its Application for Soy Milk Analysis by HPLC Method - Florentinus Dika Octa Riswanto; Alni Desra; Rinjani Mustika Sari; Valentino Thomas; Abdul Rohman; Suwidjiyo Pramono; Sudibyo Martono (Universitas Gadjah Mada, 2020)
Soy milk, one of the soybean products, become more popular in recent years due to its benefit for human health. Biological activities of soybean products have been widely studied according to the presence of isoflavone aglycones content, including genistein, daidzein, and glycitein. Hence, it is important to develop an effective and efficient analytical method to provide guidance regarding appropriate isoflavone intake levels for soy milk. A reversed-phase high performance liquid chromatography (HPLC) method was developed and optimized in this study employed by R statistical software with the package of rsm. A C18 column was used for HPLC separation with the detection at 260 nm. Optimized condition for HPLC separation has been achieved with the mobile phase of methanol: water (63.26:36.74), a flow rate of 0.81 mL/min, and a column temperature of 45.31 °C. These conditions were applied in the HPLC system and successfully tested for the system suitability. Quantitative estimation was performed and resulted that the genistein, daidzein, and glycitein content in soy milk samples were 6.372, 6.273, and 2.853 µg/mL, respectively.